Can decrease in hand grip strength in carpal tunnel syndrome be explained by interosseous muscle and intermetacarpal space dimensions? - Gökharman, Fatma Dilek; Uysal Ramadan, Selma; Aydın, Sonay; Koşar, Pınar Nercis (The European Research Journal, 2018)
Objectives. To investigate the correlation of the grip strength with sonographic measurement of interosseous muscle (IOM) and intermetacarpal space (IMS) of the hands in carpal tunnel syndrome (CTS) patients. Methods. A total of 96 hands of 48 female patients constituted the study group. Of those, 36 hands of 18 patients (mean age: 50.2 ± 9 years) had CTS confirmed by electro-diagnostic tests. Sixty hands of 30 healthy volunteers (mean age: 45.2 ± 9.7 years) constituted the control group. Grip strength was assessed by Jamar hand dynamometer. IOM and IMS dimensions for all hands were measured sonographically at three levels (2nd, 3rd and 4th intermetacarpal; palmar side for IMS, dorsal side for IOM) by the same radiologist. Spearman and Mann Whitney U tests were used for statistical analysis.Results. The median hand grip strength was determined as 11.3 kg (min-max = 7.2-18.1 kg) in the CTS group and 19.5 kg (min-max = 7.8-30.5 kg) in the control group, with a statistical difference between the two groups (p < 0.03). In both groups, there was a positive correlation between the IOM-IMS dimensions and grip strength (p < 0.05). Sonographically, IOM-IMS measurements in CTS group were significantly lower than control group (p < 0.01).Conclusion. To our knowledge, this is the first study evaluating the correlation of grip strength and the sonographic IOM-IMS measurements in CTS patients. The muscular atrophy, which is generally a finding of advanced disease, may be revealed by sonographical measurements earlier than the physical examination findings.